A Novel Swept-Back Fishnet-Embedded Microchannel Topology - Yan Wang; Xiaoyue Zhang; Xing Yang; Zhiji Wang; Yuefei Yan; Biao Du; Jiliang Zhang; Congsi Wang (Micromachines, 2023)
High in reliability, multi in function, and strong in tracking and detecting, active phased array antennas have been widely applied in radar systems. Heat dissipation is a major technological barrier preventing the realization of next-generation high-performance phased array antennas. As a result of the advancement of miniaturization and the integration of microelectronics technology, the study and development of embedded direct cooling or heat dissipation has significantly enhanced the heat dissipation effect. In this paper, a novel swept-back fishnet-embedded microchannel topology (SBFEMCT) is designed, and various microchannel models with different fishnet runner mesh density ratios and different fishnet runner layers are established to characterize the chip Tmax, runner Pmax, and Vmax and analyze the thermal effect of SBFEMCT under these two operating conditions. The Pmax is reduced to 72.37% and 57.12% of the original at mesh density ratios of 0.5, 0.25, and 0.125, respectively. The maximum temperature reduction figures are average with little change in maximum velocity and a small increase in maximum pressure drop across the number of fishnet runner layers from 0 to 4. This paper provides a study of the latest embedded thermal dissipation from the dimension of a single chip to provide a certain degree of new ideas and references for solving the thermal technology bottleneck of next-generation high-performance phased array antennas.